Implications of the number of years assessment on recommendation of common bean cultivars. Issue 5 (9th September 2015) - Ferreira, Ricardo Augusto Diniz Cabral; Ramalho, Magno Antonio Patto; Toledo, Fernando Henrique Ribeiro Barrozo; Abreu, Angela de Fátima Barbosa; Link, W.
Abstract In the common bean crop in Brazil, the requirement of the value for cultivation and use trials is that these experiments must be conducted over two years in three locations per region. Information in regard to the necessary number of years to ensure precision in cultivar recommendation and the influence of evaluated years in the estimation of the GE interaction are still scarce. Using grain yield of five check varieties assessed over 11 years in three sowing seasons per year, the aims of this study are as follows: to measure the relative contribution of the GE interaction, evaluating the implication of the number of years in the estimates of the GE interaction, and infer how many years are needed to ensure precision in cultivar recommendation. For instances, analysis of variance was carried out involving all environments and also combinations of years. The results showed that the GE interaction was greater than all other cross‐effects involving lines. The use of at least two years allows good coincidence in cultivar recommendation compared to the whole period. Increasing the evaluation time is a good strategy, especially when it is difficult to grow three different sowing seasons.